The Damage of diferent densities of M. incognita and M. javanica on tomato cv. Rio grand - A. Mussa, Mohamed; E. Ehwaeti , M.; A. El-Maleh, A. (Al-Mukhtar Journal of Sciences, 2004)
The damage due to RKN M. incognita and M. javanica on tomato (cv. Rio grande) in pots, five densities of two species (0,10, 100, 1000, 10000 juveniles/plant) were inoculated in the soil. Damage was assessed after 45 days, the results indicated when the initial population (pi) increased the growth of the plants decreased at pi 10 equal 123.2g and at the highest pi 10000 was 34.3g. Also the reproduction rate was decrease when the (pi) increased. At (pi) 10 was 144.8 and at 10000 was 1.9, but the greates final population occurred with (pi) 1000 js/plant was 37100 nematodes/plant.